The inhibitory checkpoint, PD-L2, is a target for effector T cells: Novel possibilities for immune therapy. (1st February 2018) - Ahmad, Shamaila Munir; Martinenaite, Evelina; Holmström, Morten; Jørgensen, Mia Aaboe; Met, Özcan; Nastasi, Claudia; Klausen, Uffe; Donia, Marco; Pedersen, Lars Møller; Munksgaard, Lars; Ødum, Niels; Woetmann, Anders; et al.
ABSTRACT: Cell surface molecules of the B7/CD28 family play an important role in T-cell activation and tolerance. The relevance of the PD-1/PD-L1 pathway in cancer has been extensively studied whereas PD-L2 has received less attention. However, recently the expression of PD-L2 was described to be independently associated with clinical response in anti-PD1-treated cancer patients. Here, we investigated whether PD-L2 might represent a natural target that induces specific T cells. We identified spontaneous specific T-cell reactivity against two epitopes located in the signal peptide of PD-L2 from samples from patients with cancer as well as healthy individuals ex vivo. We characterized both CD8 + and CD4 + PD-L2-specific T cells. Interestingly, the epitope in PD-L2 that elicited the strongest response was equivalent to a potent HLA-A2-restricted epitope in PD-L1. Importantly, PD-L1-specific and PD-L2-specific T cells did not cross-react; therefore, they represent different T-cell antigens. Moreover, PD-L2-specific T cells reacted to autologous target cells depending on PD-L2 expression. These results suggested that activating PD-L2 specific T cells (e.g., by vaccination) might be an attractive strategy for anti-cancer immunotherapy. Accordingly, PD-L2 specific T cells can directly support anti-cancer immunity by killing of target cells, as well as, indirectly, by releasing pro-inflammatory cytokines at the microenvironment in response to PD-L2-expressing immune supressive cells.